Qualitative analysis based reaction mechanism identification - Varga, Tamás (Acta Agraria Kaposváriensis, 2011)
One of the most important tasks during the design process of a chemical technology is the engineering design of the conversion subsystem based on the aspect of optimal and safe operation. Hence, before the design the rate of processes which have impact on the dynamic behavior of the subsystem must be identified. The reaction mechanism of a reaction system represents all the elementary reaction steps which are required to convert the reagents into products. The aim of the reaction mechanism analysis is the identification of the route how the system goes from its initial to the end state. The developed tool can be applied to identify of an unknown reaction mechanism without the necessary chemist experience. Beside, the tool can be used to determine the parameters of the rate equations of each identified chemical reaction. The first task requires structure while the second one requires parameter identification. The developed structure identification method is based on the qualitative analysis of measured and calculated state-variables trajectories, since the trends in the change of components can be easily compared based on the resulted sequences. To solve the constraint optimization problem during the parameter identification process evolutionary strategy method is applied.